1981
DOI: 10.1111/j.1365-2141.1981.tb02813.x
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Anti‐Thomsen‐Friedenreich (T) and Tn Agglutinins in Man and in White Leghorn Chicks

Abstract: Interest in anti-Thomsen-Friedenreich (T) antibodies has increased because of their significance in detection of and their possible interaction with human adenocarcinoma. The origin of anti-T, which all humans possess, has not been ascertained. We determined here that anti-T and -Tn agglutinins could readily be induced via the physiological intestinal route by an enteric bacterium, E. coli O86, which possesses T and Tn activities. One dose of live E. coli O86 given in the drinking water to germfree chicks, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

1985
1985
2012
2012

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 20 publications
0
45
0
2
Order By: Relevance
“…All individuals carry IgM antibodies against Tn and T antigens as a result of gastrointestinal bacteria carrying cross-reacting carbohydrate structures. 18 Moreover, it has been suggested that these antibodies may play a critical role in tumor surveillance. 19 It has been reported that depressed levels of anti-T IgM antibodies are associated not only with carcinoma diagnosis but also with preclinical diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…All individuals carry IgM antibodies against Tn and T antigens as a result of gastrointestinal bacteria carrying cross-reacting carbohydrate structures. 18 Moreover, it has been suggested that these antibodies may play a critical role in tumor surveillance. 19 It has been reported that depressed levels of anti-T IgM antibodies are associated not only with carcinoma diagnosis but also with preclinical diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…The T antigen (Galbeta1-3GalNAc), also known as the Thomsen-Friedenreich or Tf antigen, is exposed on red blood cells infected with viruses and bacteria or after digestion with neuramindase (146). Pioneering research conducted by George Springer led to the understanding that the majority of solid tumors express high levels of T antigen on their surface (147,148).…”
Section: Thomsen-friedenrich (T or Tf) Antigen-the Tn Antigen Was Firmentioning
confidence: 99%
“…However, in 1974. we found Tn antigen to be associated with breast carcioma [11], Tn and T are now recognized as universal ('pan') carcinoma antigens: they have been found in ~90% of all carcinomata tested from incipience onward, but they are occluded in most benign diseased and healthy tissues [12][13][14], Immunohistochemistry using computerized image analysis [15] as well as serological studies have shown that strong Tn epitope expression in primary breast carcinoma tissues is associated with poor prognosis [16][17][18], Because Tn and T epitopes are masked from the immune system in noncarcinoma tissues [1,5], all humans have anti-Tn and anti-T antibodies elicited largely by their own intestinal flora which carries Tn and T specificities [19], Since sialyl-Tn appears readily accessible only in some normal tissues, humans also have very low levels of anti-sialyl-Tn antibodies. Asialoovine submaxillary mucin (AS-OSM) was an up to > 100-fold stronger inhibitor than OSM of anti-Tn agglutinins in 56 of 58 randomly collected human sera.…”
Section: Tn Antigen Was Discovered By Moreau Et Al [I] On Polyagglutmentioning
confidence: 99%